Instructional Supervision in Nigerian Schools: Problems and Solutions - Ogunode, Niyi Jacob; Ibrahim, Abdullahi (International Journal on Integrated Education, 2023)
This paper discussed challenges hindering effective instructional supervision of schools in Nigeria. Secondary data were used in the paper. The secondary data were gathered from print materials and online publications. The paper identified poor funding, shortage of supervisors, inadequate transportation facilities, poor capacity building programme, insecurity, shortage of supervision materials, poor communication skills, corruption and political instability as challenges hindering effective instructional supervision of schools in Nigeria. The paper hereby recommended an increment in the funding of school supervision.